Outcomes of children transferring out of Red Cross War Memorial Children's Hospital HIV cohort using linkage to the National Health Laboratory Service Data - Arowosegbe, Oluwaseyi (Department of Public Health and Family Medicine, 2017)
Background and Rationale: Paediatric antiretroviral (ART) care in the Western Cape Province (WCP) has evolved following South Africa's (SA) massive roll-out of antiretroviral therapy in 2004 in response to the country's human immunodeficiency virus (HIV) epidemic. Decentralization of paediatric ART services was adopted in scaling up access to ART services for children living with HIV. Although children now mainly initiate ART at lower level facilities, sick or very young infants continue to initiate ART at tertiary health facilities and become eligible for transfer to lower level facilities after stabilization at tertiary health facilities. There has been limited assessment of the effectiveness of this model of ART care since its implementation. Aims and Objectives: The primary objective of this study is to determine the proportion of children that successfully transferred from Red Cross War Memorial Children's Hospital (RCWMCH) to referral facilities for continued ART within 18 or 48 months of their last appointment at RCWMCH. Successful transfer was defined in two ways: a laboratory test performed by a lower level facility (i) ≤18 months or (ii) ≤48 months after transfer date. The first interval corresponds to guideline recommendations for annual CD4/viral load monitoring; the second captures all children retained in care. Our secondary objectives are as follows: 1. To identify the determinants of successful transfer from RCWMCH. 2. To describe the CD4 and viral load outcomes of children that successfully transferred to referral lower health facilities within WCP. 3. To determine the feasibility of using the SA National Health Laboratory Service (NHLS) data for routine monitoring of children transferring between paediatric ART sites. Methods: A retrospective analysis of prospectively collected data was performed. The study population was children below the age of 16 years who were initiated onto ART at RCWMCH and transferred out to lower level facilities within the WCP from December 31, 2007 - January 1, 2012. We described children's characteristics before transfer out and post-transfer date. In those who successfully transferred, we compared their immunological and virological status at transfer out and at the first visit within 48 months after the transfer out date, using median change for continuous variables and difference in proportions for categorical variables. Results: Data from 1127 children with median age of 5.6 months (interquartile range [IQR] 3.1-19.9) was included; at ART initiation 85% had WHO stage III/IV disease and 57% were severely immunosuppressed. A total of 725 (64%) children were transferred; 69% (496) and 76% (541) successfully transferred within 18 and 48 months respectively. Since there is about 90% compliance with annual CD4/viral load monitoring guidelines, we estimate that up to 85% of children may have actually successfully transferred. Median time to successful transfer was 5.4 months (IQR 3.7-7.8). Among the 184 children (25%) who did not transfer successfully, 11% returned to RCWMCH. In patients who successfully transferred, median (IQR) CD4% increased between transfer out and first visit post-transfer [25.1% (17.3-33.8%) vs 30.2% (22.9-36.6%), p-value = 0.0000]. Children who had their transfer sites recorded in the database and those transferred before 2010 were identified to be associated with successful transfer (adjusted odds ratio (aOR 7.99, 95% Confidence Interval (CI) (2.3-28.5 and aOR 5.21, 95% CI 1.5-18.4 respectively). Conclusion: The proportion of children remaining in HIV care by 48 months after transfer out was at least 76% and 92% of those that transferred successfully reached the referral facility and undergoing a laboratory test within 18 months of transfer out. In children who successfully transferred, CD4% and viral load suppression improved after transfer. This suggests that paediatric ART decentralization is feasible with good outcomes. However, outcomes in those who were lost after transfer out need further investigation.